2007
DOI: 10.1016/j.exer.2006.08.010
|View full text |Cite
|
Sign up to set email alerts
|

ROM-1 potentiates photoreceptor specific membrane fusion processes

Abstract: Photoreceptor outer segment (OS) renewal requires a series of tightly regulated membrane fusion events which are mediated by a fusion complex containing protein and lipid components. The best characterized of these components, is a unique photoreceptor specific tetraspanin, peripherin/rds (P/ rds, a.k.a., peripherin-2, Rds and Prph). In these studies we investigated the role of peripherin's nonglycosylated homolog, ROM-1, in OS fusion using a COS cell heterologous expression system and a well characterized cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…38 As is evident from these studies, the loss of structural proteins has devastating effects on photoreceptor morphology and leads to loss of photoreceptors. Because Als2cr4 shares structural similarities, has a comparable immunostaining pattern, 24,34 and is embedded in the discs, we hypothesize that, similar to peripherin/rds and ROM-1, this structural protein contributes to maintaining the structural integrity of photoreceptors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…38 As is evident from these studies, the loss of structural proteins has devastating effects on photoreceptor morphology and leads to loss of photoreceptors. Because Als2cr4 shares structural similarities, has a comparable immunostaining pattern, 24,34 and is embedded in the discs, we hypothesize that, similar to peripherin/rds and ROM-1, this structural protein contributes to maintaining the structural integrity of photoreceptors.…”
Section: Discussionmentioning
confidence: 97%
“…31 In retinal disease, the most prominent members of the tetraspanin family are peripherin/rds 32,33 and ROM-1. 34 These proteins participate in outer segment morphogenesis by providing a structural basis whereby new discs and lamellae are continually added to the photoreceptor outer segment basal region. 32 The outer segment renewal is a critical process as photoreceptors undergo daily phagocytosis of apical discs and lamellae by retinal pigment epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the hypothesis that PRPH2/RDS complex formation is important for membrane fusion came from experiments showing that various disruptions in the D2 loop and blocking of PRPH2/RDS disulfide mediated oligomerization disrupted the fusogenic activity of PRPH2/RDS (Boesze-Battagliaa and Stefano, 2002). In subsequent experiments using purified PRPH2/RDS and ROM-1 expressed in COS-1 cells, it was determined that ROM-1 could not promote membrane fusion alone but did enhance PRPH2/RDS fusogenic activity when in complex with PRPH2/RDS (Boesze-Battaglia et al, 2007b). These data led to a hypothesized model in which the PRPH2/RDS tetramers, intermediate and higher-order oligomers have variable abilities to initiate membrane fusion and together are involved directly in the complicated membrane dynamics at the base of the OS (Boesze-Battaglia et al, 1997).…”
Section: Role Of Prph2/rds In the Photoreceptormentioning
confidence: 99%
“…Boesze-Battaglia and co-workers have demonstrated that Rds complexes are capable of mediating membrane fusion in vitro (34). More recently, it has been shown that Rom-1 is not capable of mediating membrane fusion alone but its presence in Rds/ Rom-1 complexes enhances Rds-mediated membrane fusion (35). The third known function of Rds in the OS is one of the focuses of this work.…”
Section: The Role Of Rds/rom-1 Complexes In Photoreceptorsmentioning
confidence: 99%